1991
DOI: 10.1002/j.1551-8833.1991.tb07234.x
|View full text |Cite
|
Sign up to set email alerts
|

Permeation of Polybutylene Pipe and Gasket Material by Organic Chemicals

Abstract: Recent investigations have found that organic chemicals may contaminate drinking water by permeating buried plastic pipes and gasket materials. Pipe-bottle direct-exposure experiments and microbalance experiments were conducted in order to determine the susceptibility of polybutylene (PB) piping material and gasket materials to permeation by a wide range of organic chemicals. Many lipophilic compounds tested were found to permeate to a detectable level in consumers' tap water within a month at one third of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 7 publications
1
12
0
Order By: Relevance
“…deionized water or salt solution), covered and periodically removed and weighed [11][12][13][14][15][16]. This was used to measure the rate at which the solution was absorbed by the polymer, as well as the diffusivity coefficient, D. Eight pieces of the polymer tube of length 14.7 cm, amounting to a total average surface area of 850 cm 2 , were inserted in a bottle and immersed in an excess of solvent.…”
Section: Sorption Testsmentioning
confidence: 99%
“…deionized water or salt solution), covered and periodically removed and weighed [11][12][13][14][15][16]. This was used to measure the rate at which the solution was absorbed by the polymer, as well as the diffusivity coefficient, D. Eight pieces of the polymer tube of length 14.7 cm, amounting to a total average surface area of 850 cm 2 , were inserted in a bottle and immersed in an excess of solvent.…”
Section: Sorption Testsmentioning
confidence: 99%
“…In addition, Berens [22] found that diffusion coefficient (D) decreases with increasing permeate weight, size (molecular volume) and cross sectional area of the penetrant. Similarly, Shao and Huang [11], reported that the diffusion coefficient of a permeate through a polymer is a strong function of the size and shape of the permeate, and Park et al [23] Hydrogen-bonding interaction has also been proposed as a dominant factor controlling the selectivity toward water in hydrophilic pervaporation process [27]. In this study, an enhanced propensity for hydrogen-bonding influenced the rejection of phenol (δh = 14.9) and 2-phenoxyethanol (δh = 14.3), as these compounds had the lowest removal of 47% and 58% respectively, whereas fluorene, which has the second lowest hydrogen bonding parameter among the seven studied compounds (δh = 1.7), was best rejected.…”
Section: Rejection Of Organic Micro-pollutantsmentioning
confidence: 89%
“…The case of benzene demonstrates that knowledge of environmental fate and transport is essential for evaluating the potential permeation risk of contaminants because the distribution of chemicals among environmental media determines the contaminant levels that plastic pipes might encounter in the field. In the unsaturated soil, plastic pipe permeation was believed to occur from the vapor phase (Holsen et al, 1991b;Park et al, 1991). The current study did not collect vapor samples for BTEX analysis, and thus the exact concentration of BTEX in soil gas was unknown during the experimental period.…”
Section: Impact Of Hydrocarbons On Pe/pvc Pipes and Pipementioning
confidence: 95%
“…No previous study specifically investigated the permeation of organic contaminants through PE pipe buried in unsaturated soil. In addition, comparing the diffusion coefficients obtained from the three permeation tests (free product gasoline, gasoline-contaminated water, and gasoline-contaminated unsaturated soil) on the basis of the values of activity is a challenge because of the lack of consistent definitions of activity (Park et al, 1991).…”
Section: Btex-benzene Toluene Ethylbenzene and Xylenementioning
confidence: 99%